Assessing potential liver injury induced by Polygonum multiflorum using potential biomarkers via targeted sphingolipidomics. (31st December 2022) - Jia, Zhixin; Liu, Lirong; Liu, Jie; Fang, Cong; Pan, Mingxia; Zhang, Jingxuan; Li, Yueting; Xian, Zhong; Xiao, Hongbin
Abstract: Context: Polygonum multiflorum Thunb. (Polygonaceae) (PM) can cause potential liver injury which is typical in traditional Chinese medicines (TCMs)-induced hepatotoxicity. The mechanism involved are unclear and there are no sensitive evaluation indicators. Objective: To assess PM-induced liver injury, identify sensitive assessment indicators, and screen for new biomarkers using sphingolipidomics. Materials and methods: Male Sprague–Dawley (SD) rats were randomly divided into four groups (control, model with low-, middle- and high-dose groups, n  = 6 each). Rats in the three model groups were given different doses of PM (i.g., low/middle/high dose, 2.7/8.1/16.2 g/kg) for four months. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in the plasma and liver were quantitatively analyzed. Fixed liver tissue sections were stained with haematoxylin and eosin and examined under a light microscope. The targeted sphingolipidomic analysis of plasma was performed using high-performance liquid chromatography tandem mass spectrometry. Results: The maximal tolerable dose (MTD) of PM administered intragastrically to mice was 51 g/kg. Sphingolipid profiling of normal and PM-induced liver injury SD rats revealed three potential biomarkers: ceramide (Cer) (d18:1/24:1), dihydroceramide (d18:1/18:0)-1-phosphate (dhCer (d18:1/18:0)-1P) and Cer (d18:1/26:1), at 867.3–1349, 383.4–1527, and 540.5–658.7 ng/mL, respectively. A criterion for the ratio of Cer (d18:1/24:1) and Cer (d18:1/26:1) was suggested and verified, with a normal range of 1.343–2.368 (with 95% confidence interval) in plasma. Conclusions: Three potential biomarkers and one criterion for potential liver injury caused by PM that may be more sensitive than ALT and AST were found.